SISTEM PEMBUKTIAN DALAM PENETAPAN PIDANA TAMBAHAN UANG PENGGANTI - Desia Rakhma Banjarani; Mada Apriandi Zuhir; Neisa Ang-rum Adisti (Jurnal Yudisial, 2025)
This article examines the application of evidentiary rules in the imposition of a compensation order as an additional penalty in corruption cases, with reference to Judgment Number 10/Pid.Sus-TPK/2015/PN.Pdg. The case concerns corruption in the procurement of a catheterization laboratory (cathlab) at the National Stroke Hospital, Bukittinggi, West Sumatra. The judgment is noteworthy because no compensation order was imposed despite the existence of state financial losses resulting from the corruption offense. Accordingly, this article analyses the legal basis for the court’s decision not to impose a compensation order and examines judicial reasoning that appears inconsistent with witness testimony. This study employs a normative legal research method using case, statutory, and conceptual approaches. The findings indicate that although the panel of judges expressly acknowledged the existence of state financial losses resulting from the defendant’s conduct, the operative part of the judgment did not impose a compensation order as an additional penalty. This outcome is inconsistent with the objective of recovering state losses as stipulated under the Anti-Corruption Law. Furthermore, the study identifies inconsistencies between judicial reasoning and witness testimony concerning the implementation of equipment testing and functional testing procedures. These inconsistencies have implications for the observance of evidentiary principles and the principle of seeking material truth. The judgment is therefore considered inconsistent with theories of justice and utility and may weaken the effectiveness of anti-corruption law enforcement.